The practice of philanthropy as a business strategy in pandemic Covid-19: a study based on of social phenomenology - Geisa Angela Batista; Fernanda Maria Boava; Carolina Machado Saraiva (Revista Eletrônica de Ciência Administrativa)
In the pandemic scenario in 2020, the emergence of philanthropic practice as a strategy on the part of organizations that sought to remain active in the market environment and, at the same time, assist hospitals in the scarcity of material and human resources caused by high demand. Thus the present work have the research problem: how the practice of philanthropy can be used as a business strategy in the period of the Covid-19 pandemic, by companies that operate in the region of Inconfidentes-MG, based of social phenomenology? The option for the methodological orientation of social phenomenology is due to this detach the motives present in the social action carried out by the subject. For this, were interviewed in a semi-structured 7 managers of companies operating in the region of Inconfidentes-MG who carried out philanthropic actions directed at Hospital Santa Casa de Ouro Preto - MG and Hospital Monsenhor Horta in Mariana - MG in 2020. It was found that the reasons why (justification) to carry out philanthropy were mixed with the subjects' personal conceptions and the reasons why (purpose) moved towards an organizational direction. The content of donations in the initial phase of the Pandemic was of an assistencialist nature, that is, the managers placed the companies themselves to meet a specific and specific demand from the Hospitals. Therefore, the managers adopted an emergent strategy and some of these companies moving towards deliberate, as the actions adopted at that moment continued for a longer time and thus integrated the organization's planning, passing the philanthropy of assistance for social investment.